RESEARCH ON BENDING FATIGUE TEST BASED ON 42CRMO GEAR (MT) - WANG JiaJun; PEI WeiChi; JI HongChao; LONG HaiYang; WANG ZhiTao (Jixie qiangdu)
42CrMo is a kind of ultra-high strength steel, which has high strength, good hardenability and small deformation after quenching. It is widely used in driving materials such as large gears, bearing spindle and connecting rod used in traction. Bending fatigue test is of great significance for fatigue life prediction of gears. First of all, the bending fatigue test data of gear under alternating load at stress ratio R=0.1 were obtained, the P-S-N curve of gear bending fatigue strength and the fitting curve relation were obtained, and the fatigue limit value of gear under different reliability was obtained. Then the finite element method was used to simulate the bending fatigue test of gear. The static strength at the root of the gear tooth is compared with the theoretical value, and the analysis shows that the numerical simulation results are basically consistent with the theoretical analysis results, which can be used as the basis of fatigue life simulation of bending fatigue test. Finally, the experimental values of the bending fatigue life test are compared with the numerical simulation results. The results show that the fatigue life test values are basically consistent with the numerical simulation results when the reliability is 84.1%, which verifies the accuracy of the numerical simulation and can effectively predict the bending fatigue life of 42CrMo gear.